Diagnostics and Prognostics‐Oriented Modeling of an NGSR Fuel Processor for Application in SOFC Systems1. Issue 4 (5th May 2017) - Pugliese, F.; Trucco, A.; Moser, G.; Costamagna, P.
Abstract: Diagnostics and prognostics of natural gas steam reforming (NGSR) reactors are of utmost importance for solid oxide fuel cell (SOFC) systems, where a fuel processor fault can cause damage to the SOFC stack. Most common faults are due to carbon deposition. We investigate this phenomenon through a model based on microscopic mass, energy and momentum balances of a tubular NGSR reactor. The model includes a detailed local reaction kinetics specific for Ni‐based catalysts, and is integrated numerically using a finite element method (FEM) implemented through COMSOL Multiphysics 5.2. Results obtained from the simulation of a laboratory scale reactor are validated on the basis of literature data. Furthermore, the model is applied to an NGSR fuel processor designed for an 1.1 kW SOFC system. The model allows to identify the area where carbon deposition is expected to occur, which is a key feature in view of developing specific diagnostic and prognostic tools. The simulation results demonstrate that safety criteria based on the feedstock steam to carbon (S/C) ratio can be misleading in a number of operating conditions.